2017
DOI: 10.1111/cea.12889
|View full text |Cite
|
Sign up to set email alerts
|

Maternal psychiatric symptoms during pregnancy and risk of childhood atopic diseases

Abstract: SummaryBackground Maternal psychiatric symptoms during pregnancy might affect the developing immune system and subsequent risk of childhood atopic diseases. Objective Our aim was to examine the associations of maternal psychiatric symptoms during pregnancy with allergic sensitization, allergy and eczema in children until age 10 years. Methods This study among 5205 children was performed in a population-based prospective cohort from foetal life onwards. We assessed maternal and paternal psychiatric symptoms (ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(76 citation statements)
references
References 37 publications
(54 reference statements)
1
72
2
1
Order By: Relevance
“…Perceived, preconception stress was significantly associated with offspring eczema at age 12 months but not at 6 months (see front cover of this issue of the journal). This chimes with data published earlier this year linking maternal psychiatric disease during pregnancy with offspring eczema [6].…”
supporting
confidence: 89%
“…Perceived, preconception stress was significantly associated with offspring eczema at age 12 months but not at 6 months (see front cover of this issue of the journal). This chimes with data published earlier this year linking maternal psychiatric disease during pregnancy with offspring eczema [6].…”
supporting
confidence: 89%
“…Interestingly, some studies have indicated that maternal stress during pregnancy may play a significant role in the development of AD in offspring. It is possible that in cases where pregnant women suffer not only from AD but also from depression or psychosomatic disorders, the offspring have a significantly higher risk of developing AD up to the age of 18–20 years . Possible psycho‐immunological pathways are changes in cytokine levels or oxidative stress transferred by the placenta .…”
Section: Factors That May Explain Change In Atopic Dermatitis Severitmentioning
confidence: 99%
“…Allergen intake has been used as a marker for diet diversity . The study found no consistent association between timing and diversity of allergenic solid food introduction and allergic sensitization, physician‐diagnosed food allergy or eczema up to 10 y of age.…”
Section: Introductionmentioning
confidence: 89%